TEMPS-A Temperament Scale Before and After Septoplasty in Patients with Nasal Septum Deviation - Yüce, Salim (Springer-Verlag, 2012)
The present study aimed to evaluate whether patients undergoing an operation for septum deviation exhibited a change in affective status. The temperament evaluation of the Memphis, Pisa, Paris, and San Diego Autoquestionnaire (TEMPS-A) was administered to all patients at the pre-operative and post-operative periods. The mean age of the patients was 32.46 ± 11.22 years. Of the patients, 34 (65.4%) were males and 18 (34.6%) were females. A significant difference was found between pre- and post-operative scores of the patients on all TEMPS-A subscales (p < 0.05). Patients with symptoms of upper airway obstruction may have mood disorders due to the decrease in blood oxygen levels. This condition can be corrected with septoplasty procedure. In the present study, it was demonstrated that patients had a better affective status post-operatively as compared to the pre-operative period. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12070-012-0526-5) contains supplementary material, which is available to authorized users.